Comparison of aerobic capacity and somatic characteristics between competitive youth mountain bikers and road cyclists - Zaton, M.; Dabrowski, D.; Bugajski, A. (Medicina Sportiva, 2014)
Objective: To compare the anthropometric characteristics of mountain bicycle riders (MTB) and road cyclists and identify the somatic variables that affect aerobic capacity. Methods: 100 males aged 16-18 years involved in professional mountain (n = 25) and road (n = 75) cycling for 2-5 years were recruited. Initial measurements of arterial blood pressure, body height, body mass, and body composition were taken. Aerobic capacity was measured in terms of respiratory function and work done (W) during a graded exercise test on a cycle ergometer. Analysis was performed on seven somatic variables (including body composition), maximal oxygen uptake, W, and body mass index. Basic statistical methods were employed, including Student`s t-test for independent samples and cluster analysis. Results: Cluster analysis found that W was the last variable that merged with the other analyzed parameters, suggesting that it can be regarded as a universal indicator of physical fitness among cyclists. The MTB performed significantly less W and featured lower values of body water percentage, fat-free mass, body mass, and body height. This group also had lower absolute values of oxygen consumption and was characterized by having less body fat than the road cyclists. Conclusions: When compared with road cyclists, MTB riders have lower body height and body mass and less fat mass and fat-free mass, giving them an advantage in uphill climbing. The criteria for selecting competitive cyclists should include not only